The moral economy of heroin in ‘Austerity Britain’ - Wakeman, Stephen (Critical criminology, 2016)
This article presents the findings of an ethnographic exploration of heroin use in a disadvantaged area of the United Kingdom. Drawing on developments in continental philosophy as well as debates around the nature of social exclusion in the late-modern west, the core claim made here is that the cultural systems of exchange and mutual support which have come to underpin heroin use in this locale - that, taken together, form a ‘moral economy of heroin’ - need to be understood as an exercise in reconstituting a meaningful social realm by, and specifically for, this highly marginalised group. The implications of this claim are discussed as they pertain to the fields of drug policy, addiction treatment, and critical criminological understandings of disenfranchised groups.